Interview with Eduardo Mora-Castellanos. Journals: new sources for alternative environmental education. - Pizarro Méndez, Yanina (2016)
“Environmental journals, for what?” seems to be the main premise of the interview to Dr. Eduardo Mora Castellanos, former editor of successful journals such as Ambientales -today known as Revista de Ciencias Ambientales-, and the popular Ambientico. Questions and confessions in the following pages present the evolution of environmental education at the National University of Costa Rica, and the parallelisms with the foundation of specialized journals that were knowledge builders of university professors, students and citizens wishing to understand the causes of national environmental issues, and, especially, possible academic proposals in order to choose a needed environmental resilience.